Academic Supervision at SMA Negeri 18 Palembang - Maryati, Eka Rahmi (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
Minister of National Education Regulation Number 13 of 2007 explains the ability of school principals to understand the Competency Standards of School Principals. The competence of the school principal based on the Minister of National Education Regulation consists of four components. The competency of the principal is an absolute ability to be mastered and practiced by the principal to lead and guide his subordinates within the scope of the school. One form of application is to carry out supervision competencies. This competency is a real action by the principal to improve the professionalism of teachers. The content of the activity is to approach using appropriate supervision techniques and then follow up. Looking at the results of the analysis of the supervision program in general at SMAN 18 Palembang, it should be followed up in order to improve the quality of educators such as: teachers have not developed and implemented an active learning process, teachers’ understanding of creative learning activities has not been maximized, and learning indicators and programs have not been developed holistically. It is an obligation for the principal to carry out comprehensive and systematic supervision and detail the opportunities for activities to be held along with the feedback from the supervision activities carried out. It is expected to boost the quality of learning for teachers and students in the classroom.